High-thermal-conductivity core-shell copper-zinc-aluminum catalyst, preparation method thereof and application of catalyst in methanol reforming hydrogen production reaction
By preparing a high thermal conductivity core-shell copper-zinc-aluminum catalyst, the problem of poor thermal conductivity of copper-based catalysts was solved, a more efficient catalytic effect in the methanol steam reforming hydrogen production reaction was achieved, and the methanol conversion rate was improved.
Patent Information
- Application Number
- CN202510788099.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-13
- Publication Date
- 2025-09-05
AI Technical Summary
Existing copper-based catalysts have poor thermal conductivity in the methanol steam reforming hydrogen production reaction, resulting in uneven bed temperature, affecting catalytic activity and accelerating the sintering of active components.
A high thermal conductivity core-shell copper-zinc-aluminum catalyst is used, and the thermal conductor is embedded between copper oxide, zinc oxide and aluminum oxide through precipitation method, forming a structure with the thermal conductor as the core and the active component as the shell, realizing micro-mixing of nanoparticles such as copper and zinc oxide with the thermal conductor, thereby enhancing heat transfer.
The thermal conductivity of the catalyst is improved, the temperature unevenness is reduced, the catalytic activity is enhanced, the methanol conversion rate is increased, and a stronger catalytic effect is shown.
Smart Images

Figure CN120586941A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst preparation, and in particular to a high-thermal-conductivity core-shell copper-zinc-aluminum catalyst, a preparation method thereof, and application thereof in a methanol reforming hydrogen production reaction. Background Art
[0002] Among the many hydrogen production methods, methanol steam reforming (MHR) offers advantages such as low reaction temperature, high hydrogen purity, low investment costs, and convenient raw material transportation and storage. Currently, two main types of catalysts have been reported for methanol reforming hydrogen production: non-precious metal catalysts and precious metal catalysts. Among non-precious metal catalysts, copper-based catalysts are currently the preferred choice for methanol steam reforming hydrogen production due to their high reforming activity, high hydrogen selectivity, and low cost.
[0003] Researchers are currently conducting extensive research on improving the catalytic activity of copper-based catalysts, primarily focusing on employing novel preparation methods or formulations to enhance the intrinsic activity of the catalysts. However, methanol steam reforming is a highly endothermic reaction, and granular catalysts have poor thermal conductivity, resulting in significant heat transfer resistance during the catalytic methanol steam reforming reaction. This low thermal conductivity of the catalyst can easily lead to uneven temperatures within the bed, resulting in hot and cold spots, which in turn affect catalytic activity and accelerate the sintering of active components.
[0004] Currently, for strongly endothermic or exothermic reactions, adding a thermal conductor to the catalyst is often used. For example, Chinese Patent No. 103831131 B mixes a calcined heteropolyacid catalyst precursor with a thermal conductor to remove the exothermic heat from methacrylic acid synthesis. Chinese Patent No. 116212950 B supports the catalyst within porous metal thermally conductive particles for the low-temperature, low-pressure preparation of glycolide. Because the catalytic reaction occurs within the catalyst's microstructure, such as the surface of metal nanoparticles or the interface of metal oxides, traditional addition methods only achieve physical mixing of the catalyst particles and the thermal conductor at a macroscopic level, failing to transfer or remove heat to the active centers through the thermal conductor.
[0005] In view of the strong endothermic characteristics of the methanol reforming hydrogen production reaction, this application designs and prepares a copper-zinc-aluminum catalyst with a thermal conductor as the core and copper, zinc oxide and aluminum oxide nanoparticles as the shell. The metal salt is precipitated in situ on the surface of the thermal conductor to achieve microscopic mixing of nanoparticles such as copper and zinc oxide with the thermal conductor, which is conducive to enhancing heat transfer at the nanoscale. Compared with other methods of adding thermal conductors, such as particle mixing and tablet mixing, it shows a stronger catalytic effect in strongly endothermic reactions such as methanol steam reforming hydrogen production reaction. Summary of the Invention
[0006] In view of the problems existing in the prior art, the purpose of the present invention is to provide a high-thermal-conductivity core-shell copper-zinc-aluminum catalyst, its preparation method, and its application in methanol reforming hydrogen production reactions. The catalyst can enhance heat transfer at the nanoscale, exhibit a stronger catalytic effect on strongly endothermic reactions such as methanol steam reforming hydrogen production, and the preparation process is simple and easy to operate.
[0007] To achieve the above object, the technical solution of the present invention is as follows: The present invention proposes a high thermal conductivity core-shell copper-zinc-aluminum catalyst. The catalyst has a core-shell structure and includes a thermal conductor, copper, zinc oxide and aluminum oxide nanoparticles. The thermal conductor is embedded between copper oxide, zinc oxide and aluminum oxide to form a catalyst structure with the thermal conductor as the core and the copper, zinc oxide and aluminum oxide nanoparticles as the shell.
[0008] The present invention proposes a method for preparing a high thermal conductivity core-shell copper-zinc-aluminum catalyst. The catalyst is prepared by a precipitation method, and the active component is in situ deposited on the surface of a thermal conductor, so that the thermal conductor is uniformly mixed with the catalyst active structure at the nanoscale to form a core-shell structure, with the thermal conductor as the core and the active component as the shell. The method specifically includes the following steps: S1: Add the thermal conductive agent to a certain amount of deionized water and ultrasonically disperse it to obtain a suspension; S2: Dissolve the copper source, zinc source, and aluminum source in deionized water according to the feed ratio and stir evenly to obtain metal salt solution A; dissolve the alkali in deionized water to obtain solution B; S3: adding the metal salt solution A and solution B obtained in step S2 to the suspension obtained in step S1 in parallel, causing the metal salt to undergo an in-situ precipitation reaction on the thermal conductor. After the precipitation is completed, the mixture is aged under stirring. After the aging is completed, the mixture is filtered, washed, and dried to obtain a catalyst precursor. S4: calcining the precursor obtained in step S3 in a muffle furnace to obtain an oxidized copper-zinc-aluminum catalyst; then performing a reduction treatment on the oxidized copper-zinc-aluminum catalyst to obtain a core-shell copper-zinc-aluminum catalyst with high thermal conductivity.
[0009] Furthermore, in step S1, the thermal conductor is one or more of silicon carbide, carbon black, silicon dioxide, graphite, copper powder, and iron powder, the mass fraction of the thermal conductor is 5-50%, and the particle size of the thermal conductor powder is less than 200 mesh.
[0010] Furthermore, in step S2, the copper source is one or more of copper acetate, copper nitrate, copper chloride, and copper sulfate; the zinc source is one or more of zinc acetate, zinc nitrate, zinc chloride, and zinc sulfate; the aluminum salt is one or more of aluminum nitrate, aluminum chloride, and aluminum sulfate; and the components in the catalyst are expressed in molar percentages as follows: Cu is 20-80%, Zn is 10-60%, and Al is 1-20%.
[0011] Furthermore, in step S2, the alkali is one or more of sodium hydroxide, sodium carbonate, sodium bicarbonate, ammonia water, etc., wherein the concentration of the alkali is 0.5-4 mol / L.
[0012] Furthermore, the specific process of step S3 is as follows: The metal salt solution A and solution B obtained in step S2 are added to the suspension obtained in step S1 at the same time, and the addition process is accompanied by stirring and 40-80 o C water bath heating and maintain the bottom liquid pH value at 6~8, after adding, aging for 0.5~4 h, keep stirring and water bath heating during the aging process, after the aging is completed, use deionized water to wash the precipitate until no sodium ions are detected in the filtrate, and then precipitate at 90~120 o C for 4 to 24 h to obtain a catalyst precursor.
[0013] Furthermore, the calcination temperature in step S4 is 300-500 o C, the calcination time is 2~6 h, the heating rate is 2~5 o C / min.
[0014] Furthermore, in step S4, the calcined oxidized copper-zinc-aluminum catalyst is treated under a reducing atmosphere, wherein the treatment atmosphere is a diluted H2 atmosphere, wherein H2 accounts for 10%-50% of the volume ratio of the mixed gas, and the rest is an inert atmosphere of N2, Ar, and He, and the heating rate is 2-5 o C / min, processing temperature is 200~300 o C, processing time is 2~4 h.
[0015] The present invention also proposes the use of a high thermal conductivity core-shell copper-zinc-aluminum catalyst prepared by the method in a methanol reforming hydrogen production reaction.
[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: 1) The present invention co-precipitates copper, zinc, and aluminum on a thermal conductive agent, achieving microscopic mixing of nanoparticles of copper and zinc oxide with the thermal conductive agent. This facilitates enhanced heat transfer at the nanoscale. The addition of the thermal conductive agent also facilitates the dispersion of copper and zinc species, resulting in a stronger catalytic effect for strongly endothermic reactions such as methanol steam reforming to produce hydrogen. 2) The copper-zinc-aluminum catalyst prepared by the method of the present invention, using a suspension of powdered graphite and water as a precipitation base, has good activity and a high methanol conversion rate of 51.5% in the methanol reforming hydrogen production reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is the EDS-Mapping diagram of the catalyst prepared in Example 5 of the present invention; Figure 2 Schematic diagram of the structure of the catalyst of the present invention. DETAILED DESCRIPTION
[0018] The present invention will be further described below with reference to the embodiments, but the scope of protection of the present invention is not limited to the described scope.
[0019] Example 1
[0020] S1: First, add 14.50 g of copper nitrate trihydrate, 8.92 g of zinc nitrate hexahydrate, and 3.75 g of aluminum nitrate nonahydrate in a molar ratio of 6:3:1 to 100 g of water and stir to mix thoroughly; S2: Weigh 10.70 g of sodium carbonate (the same number of moles as the total number of the three metals) into 100 g of water and stir to mix thoroughly; S3: Add 0.39 g of powdered carbon black to 100 g of water and stir until a uniform suspension is formed, which serves as the coprecipitation base liquid; S4: Add the metal salt solution of step S1 and the sodium carbonate solution of step S2 to the precipitation bottom solution of step S3 simultaneously, and stir and heat for 20 minutes. o C water bath and maintain the pH value of the bottom solution at 7 ± 0.5; after adding, age for 4 h, keep stirring and water bath heating during the aging process; after the aging, wash the precipitate with deionized water until no sodium ions are detected in the filtrate; then, heat the precipitate at 100 o C for 8 h to obtain the precursor; S5: Grind the precursor into powder and heat it in air at 300 o C was calcined for 0.5 h at a heating rate of 2 o C / min; S6: After calcination, the catalyst was crushed into 40-60 mesh granular catalyst and heated to 250°C in a 10% H2-90% N2 atmosphere. o C for 3 h, and the heating rate was 3 o C / min to obtain copper-zinc-aluminum catalyst.
[0021] Example 2
[0022] S1: First, add 19.33 g of copper nitrate trihydrate, 5.65 g of zinc nitrate hexahydrate, and 0.38 g of aluminum nitrate nonahydrate in a molar ratio of 8:1.9:0.1 to 100 g of water and stir to mix thoroughly; S2: Weigh 10.70 g of sodium carbonate (the same number of moles as the total number of the three metals) into 100 g of water and stir to mix thoroughly; S3: Add 4.21 g of powdered silicon carbide to 100 g of water and stir until a uniform suspension is formed, which serves as the coprecipitation base liquid; S4: Add the metal salt solution of step S1 and the sodium carbonate solution of step S2 to the precipitation bottom solution of step S3 simultaneously, and stir and heat for 80 minutes. o C water bath and maintain the pH value of the bottom solution at 6.5 ± 0.5; age for 0.5 h after addition, and keep stirring and water bath heating during the aging process; after the aging, wash the precipitate with deionized water until no sodium ions are detected in the filtrate; then cool the precipitate at 120 o C for 24 h to obtain the precursor; S5: Grind the precursor into powder and heat it in air at 450 o C was calcined for 6 h at a heating rate of 5 o C / min; S6: After calcination, the catalyst was crushed into 40-60 mesh granular catalyst and heated to 300°C in 50% H2-50% N2 atmosphere. o C for 4 h, and the heating rate was 5 o C / min to obtain copper-zinc-aluminum catalyst.
[0023] Example 3
[0024] S1: First, add 4.84 g of copper nitrate trihydrate, 17.84 g of zinc nitrate hexahydrate, and 7.50 g of aluminum nitrate nonahydrate in a molar ratio of 2:6:2 to 100 g of water and stir to mix thoroughly; S2: Weigh 10.70 g of sodium carbonate (the same number of moles as the total number of the three metals) into 100 g of water and stir to mix thoroughly; S3: Add 1.50 g of powdered silicon carbide to 100 g of water and stir until a uniform suspension is formed, which serves as the coprecipitation base liquid; S4: Add the metal salt solution of step S1 and the sodium carbonate solution of step S2 to the precipitation bottom solution of step S3 simultaneously, and stir and heat for 20 minutes. o C water bath and maintain the pH value of the bottom solution at 7.5 ± 0.5; after adding, age for 4 h, stirring and water bath heating are maintained during the aging process; after the aging, the precipitate is washed with deionized water until no sodium ions are detected in the filtrate; the precipitate is then heated at 90 o C for 20 h to obtain the precursor; S5: Grind the precursor into powder and heat it in air at 400 o C was calcined for 4 h at a heating rate of 3 o C / min; S6: After calcination, the catalyst was crushed into 40-60 mesh granular catalyst and heated to 200°C in 5% H2-95% N2 atmosphere. o C for 2 h, and the heating rate was 5 oC / min to obtain copper-zinc-aluminum catalyst.
[0025] Example 4
[0026] S1: First, add 16.92 g of copper nitrate trihydrate, 5.95 g of zinc nitrate hexahydrate, and 3.75 g of aluminum nitrate nonahydrate in a molar ratio of 7:2:1 to 100 g of water and stir to mix thoroughly; S2: Weigh 10.70 g of sodium carbonate (the same number of moles as the total number of the three metals) into 100 g of water and stir to mix thoroughly; S3: Add 7.71 g of powdered graphite to 100 g of water and stir until a uniform suspension is formed, which serves as the coprecipitation base liquid; S4: Add the metal salt solution of step S1 and the sodium carbonate solution of step S2 to the precipitation bottom solution of step S3 simultaneously, and stir and heat for 60 minutes. o C water bath and maintain the pH value of the bottom solution at 7 ± 0.5; after adding, age for 3 h, stirring and water bath heating are maintained during the aging process; after the aging, the precipitate is washed with deionized water until no sodium ions are detected in the filtrate; the precipitate is then heated at 120 o C for 24 h to obtain the precursor; S5: Grind the precursor into powder and heat it in air at 350 o C was calcined for 3 h at a heating rate of 3 o C / min; S6: After calcination, the catalyst was crushed into 40-60 mesh granular catalyst and heated in 20% H2-80% N2 atmosphere for 300 o C for 3 h, and the heating rate was 3 o C / min to obtain copper-zinc-aluminum catalyst.
[0027] Example 5
[0028] S1: First, add 14.50 g of copper nitrate trihydrate, 8.92 g of zinc nitrate hexahydrate, and 3.75 g of aluminum nitrate nonahydrate in a molar ratio of 6:3:1 to 100 g of water and stir to mix thoroughly; S2: Weigh 10.70 g of sodium carbonate (the same number of moles as the total number of the three metals) into 100 g of water and stir to mix thoroughly; S3: Add 1.55 g of powdered silicon carbide to 100 g of water and stir until a uniform suspension is formed, which serves as the coprecipitation base liquid; S4: Add the metal salt solution of step S1 and the sodium carbonate solution of step S2 to the precipitation bottom solution of step S3 at the same time, stirring and stirring at 70 oC water bath and maintain the pH value of the bottom solution at 7 ± 0.5; after adding, age for 2 h, keep stirring and water bath heating during the aging process; after the aging, wash the precipitate with deionized water until no sodium ions are detected in the filtrate; then, heat the precipitate at 110 o C for 12 h to obtain the precursor; S5: Grind the precursor into powder and heat it in air at 350 o C was calcined for 4 h at a heating rate of 3 o C / min; S6: After calcination, the catalyst was crushed into 40-60 mesh granular catalyst and heated to 250°C in 10% H2-90% N2 atmosphere. o C for 3 h, and the heating rate was 3 o C / min to obtain copper-zinc-aluminum catalyst.
[0029] Example 6
[0030] S1: First, add 14.50 g of copper nitrate trihydrate, 8.92 g of zinc nitrate hexahydrate, and 3.75 g of aluminum nitrate nonahydrate in a molar ratio of 6:3:1 to 100 g of water and stir to mix thoroughly; S2: Weigh 10.70 g of sodium carbonate (the same number of moles as the total number of the three metals) into 100 g of water and stir to mix thoroughly; S3: Add 1.55 g of powdered graphite to 100 g of water and stir until a uniform suspension is formed, which serves as the coprecipitation base liquid; S4: Add the metal salt solution of step S1 and the sodium carbonate solution of step S2 to the precipitation bottom solution of step S3 at the same time, stirring and stirring at 70 o C water bath and maintain the pH value of the bottom solution at 7 ± 0.5; after adding, age for 2 h, keep stirring and water bath heating during the aging process; after the aging, wash the precipitate with deionized water until no sodium ions are detected in the filtrate; then, heat the precipitate at 110 o C for 12 h to obtain the precursor; S5: Grind the precursor into powder and heat it in air at 350 o C was calcined for 4 h at a heating rate of 3 o C / min; S6: After calcination, the catalyst was crushed into 40-60 mesh granular catalyst and heated to 250°C in 10% H2-90% N2 atmosphere. o C for 3 h, and the heating rate was 3 o C / min to obtain copper-zinc-aluminum catalyst.
[0031] Example 7
[0032] S1: First, add 14.50 g of copper nitrate trihydrate, 8.92 g of zinc nitrate hexahydrate, and 3.75 g of aluminum nitrate nonahydrate in a molar ratio of 6:3:1 to 100 g of water and stir to mix thoroughly; S2: Weigh 10.70 g of sodium carbonate (the same number of moles as the total number of the three metals) into 100 g of water and stir to mix thoroughly; S3: Add 4.65 g of powdered silicon carbide to 100 g of water and stir until a uniform suspension is formed, which serves as the coprecipitation base liquid; S4: Add the metal salt solution of step S1 and the sodium carbonate solution of step S2 to the precipitation bottom solution of step S3 at the same time, stirring and stirring at 70 o C water bath and maintain the pH value of the bottom solution at 7 ± 0.5; after adding, age for 2 h, keep stirring and water bath heating during the aging process; after the aging, wash the precipitate with deionized water until no sodium ions are detected in the filtrate; then, heat the precipitate at 110 o C for 12 h to obtain the precursor; S5: Grind the precursor into powder and heat it in air at 350 o C was calcined for 4 h at a heating rate of 3 o C / min; S6: After calcination, the catalyst was crushed into 40-60 mesh granular catalyst and heated to 250°C in a 10% H2-90% N2 atmosphere. o C for 3 h, and the heating rate was 3 o C / min to obtain copper-zinc-aluminum catalyst.
[0033] Example 8
[0034] S1: First, add 14.50 g of copper nitrate trihydrate, 8.92 g of zinc nitrate hexahydrate, and 3.75 g of aluminum nitrate nonahydrate in a molar ratio of 6:3:1 to 100 g of water and stir to mix thoroughly; S2: Weigh 10.70 g of sodium carbonate (the same number of moles as the total number of the three metals) into 100 g of water and stir to mix thoroughly; S3: Add 1.55 g of powdered hydrophilic silica to 100 g of water and stir until a uniform suspension is formed, which serves as the coprecipitation base liquid; S4: Add the metal salt solution of step S1 and the sodium carbonate solution of step S2 to the precipitation bottom solution of step S3 at the same time, stirring and stirring at 70 o C water bath and maintain the pH value of the bottom solution at 7 ± 0.5; after adding, age for 2 h, keep stirring and water bath heating during the aging process; after the aging, wash the precipitate with deionized water until no sodium ions are detected in the filtrate; then, heat the precipitate at 110 oC for 12 h to obtain the precursor; S5: Grind the precursor into powder and heat it in air at 350 o C was calcined for 4 h at a heating rate of 3 o C / min; S6: After calcination, the catalyst was crushed into 40-60 mesh granular catalyst and heated to 250°C in 10% H2-90% N2 atmosphere. o C for 3 h, and the heating rate was 3 o C / min to obtain copper-zinc-aluminum catalyst.
[0035] Example 9
[0036] S1: First, add 13.06 g of copper acetate monohydrate, 5.50 g of zinc acetate, and 3.75 g of aluminum nitrate nonahydrate to 100 g of water in a molar ratio of 6:3:1 and stir to mix thoroughly. S2: Weigh 10.70 g of sodium carbonate (the same number of moles as the total number of the three metals) into 100 g of water and stir to mix thoroughly; S3: Add 1.55 g of powdered silicon carbide to 100 g of water and stir until a uniform suspension is formed, which serves as the coprecipitation base liquid; S4: Add the metal salt solution of step S1 and the sodium carbonate solution of step S2 to the precipitation bottom solution of step S3 at the same time, stirring and stirring at 70 o C water bath and maintain the pH value of the bottom solution at 7 ± 0.5; after adding, age for 2 h, keep stirring and water bath heating during the aging process; after the aging, wash the precipitate with deionized water until no sodium ions are detected in the filtrate; then, heat the precipitate at 110 o C for 12 h to obtain the precursor; S5: Grind the precursor into powder and heat it in air at 350 o C was calcined for 4 h at a heating rate of 3 o C / min; S6: After calcination, the catalyst was crushed into 40-60 mesh granular catalyst and heated to 250°C in 10% H2-90% N2 atmosphere. o C for 3 h, and the heating rate was 3 o C / min to obtain copper-zinc-aluminum catalyst.
[0037] Example 10
[0038] S1: First, add 14.50 g of copper nitrate trihydrate, 8.92 g of zinc nitrate hexahydrate, and 3.75 g of aluminum nitrate nonahydrate in a molar ratio of 6:3:1 to 100 g of water and stir to mix thoroughly; S2: Weigh 10.70 g of sodium carbonate (the same number of moles as the total number of the three metals) into 100 g of water and stir to mix thoroughly; S3: Add 0.39 g of powdered silicon carbide to 100 g of water and stir until a uniform suspension is formed, which serves as the coprecipitation base liquid; S4: Add the metal salt solution of step S1 and the sodium carbonate solution of step S2 to the precipitation bottom solution of step S3 at the same time, stirring and stirring at 70 o C water bath and maintain the pH value of the bottom solution at 7 ± 0.5; after adding, age for 2 h, keep stirring and water bath heating during the aging process; after the aging, wash the precipitate with deionized water until no sodium ions are detected in the filtrate; then, heat the precipitate at 110 o C for 12 h to obtain the precursor; S5: Grind the precursor into powder and heat it in air at 350 o C was calcined for 4 h at a heating rate of 3 o C / min; S6: After calcination, the catalyst was crushed into 40-60 mesh granular catalyst and heated to 250°C in 10% H2-90% N2 atmosphere. o C for 3 h, and the heating rate was 3 o C / min to obtain copper-zinc-aluminum catalyst.
[0039] Example 11
[0040] S1: First, add 10.23 g of copper chloride dihydrate, 4.09 g of zinc chloride, and 1.33 g of aluminum chloride in a molar ratio of 6:3:1 to 100 g of water and stir to mix thoroughly; S2: Weigh 10.70 g of sodium carbonate (the same number of moles as the total number of the three metals) into 100 g of water and stir to mix thoroughly; S3: Add 1.55 g of powdered silicon carbide to 100 g of water and stir until a uniform suspension is formed, which serves as the coprecipitation base liquid; S4: Add the metal salt solution of step S1 and the sodium carbonate solution of step S2 to the precipitation bottom solution of step S3 at the same time, stirring and stirring at 70 o C water bath and maintain the pH value of the bottom solution at 7 ± 0.5; after adding, age for 2 h, keep stirring and water bath heating during the aging process; after the aging, wash the precipitate with deionized water until no sodium ions are detected in the filtrate; then, heat the precipitate at 110 o C for 12 h to obtain the precursor; S5: Grind the precursor into powder and heat it in air at 350 o C was calcined for 4 h at a heating rate of 3 o C / min; S6: After calcination, the catalyst was crushed into 40-60 mesh granular catalyst and heated to 250°C in a 10% H2-90% N2 atmosphere.o C for 3 h, and the heating rate was 3 o C / min to obtain copper-zinc-aluminum catalyst.
[0041] Comparative Example 1 S1: First, add 14.50 g of copper nitrate trihydrate, 8.92 g of zinc nitrate hexahydrate, and 3.75 g of aluminum nitrate nonahydrate in a molar ratio of 6:3:1 to 100 g of water and stir to mix thoroughly; S2: Weigh 10.70 g of sodium carbonate (the same number of moles as the total number of the three metals) into 100 g of water and stir to mix thoroughly; S3: Add 1.55 g of copper powder to 100 g of water and stir until a uniform suspension is formed, which serves as the coprecipitation base solution. S4: Add the metal salt solution of step S1 and the sodium carbonate solution of step S2 to the precipitation bottom solution of step S3 at the same time, stirring and stirring at 70 o C water bath and maintain the pH value of the bottom solution at 7 ± 0.5; after adding, age for 2 h, keep stirring and water bath heating during the aging process; after the aging, wash the precipitate with deionized water until no sodium ions are detected in the filtrate; then, heat the precipitate at 110 o C for 12 h to obtain the precursor; S5: Grind the precursor into powder and heat it in air at 350 o C was calcined for 4 h at a heating rate of 3 o C / min; S6: After calcination, the catalyst was crushed into 40-60 mesh granular catalyst and heated to 250°C in 10% H2-90% N2 atmosphere. o C for 3 h, and the heating rate was 3 o C / min to obtain a mixed catalyst.
[0042] The difference from Example 5 is that the thermal conductive agent used is copper powder, which has strong thermal conductivity but poor hydrophilicity and will quickly settle when forming a suspension with deionized water.
[0043] Comparative Example 2 S1: First, add 14.50 g of copper nitrate trihydrate, 8.92 g of zinc nitrate hexahydrate, and 3.75 g of aluminum nitrate nonahydrate in a molar ratio of 6:3:1 to 100 g of water and stir to mix thoroughly; S2: Weigh 10.70 g of sodium carbonate (the same number of moles as the total number of the three metals) into 100 g of water and stir to mix thoroughly; S3: Add 1.55 g of powdered quartz sand to 100 g of water and stir until a uniform suspension is formed, which serves as the coprecipitation base liquid; S4: Add the metal salt solution of step S1 and the sodium carbonate solution of step S2 to the precipitation bottom solution of step S3 at the same time, stirring and stirring at 70 o C water bath and maintain the pH of the bottom solution at 7 ± 0.5; after adding, age for 2 h, keep stirring and water bath heating during the aging process; after the aging, wash the precipitate with deionized water until no sodium ions are detected in the filtrate; then, heat the precipitate at 110 o C for 12 h to obtain the precursor; S5: Grind the precursor into powder and heat it in air at 350 o C was calcined for 4 h at a heating rate of 3 o C / min; S6: After calcination, the catalyst was crushed into 40-60 mesh granular catalyst and heated to 250°C in 10% H2-90% N2 atmosphere. o C for 3 h, and the heating rate was 3 o C / min to obtain a mixed catalyst.
[0044] The difference from Example 5 is that the thermal conductive agent used is quartz sand, which has poor thermal conductivity and hydrophilicity.
[0045] Comparative Example 3 S1: First, add 14.50 g of copper nitrate trihydrate, 8.92 g of zinc nitrate hexahydrate, and 3.75 g of aluminum nitrate nonahydrate in a molar ratio of 6:3:1 to 100 g of water and stir to mix thoroughly; S2: Weigh 10.70 g of sodium carbonate (the same number of moles as the total number of the three metals) into 100 g of water and stir to mix thoroughly; S3: Use 100 mL of deionized water as the precipitation base solution; S4: Add the metal salt solution of step S1 and the sodium carbonate solution of step S2 to the precipitation bottom solution of step S3 at the same time, stirring and stirring at 70 o C water bath and maintain the pH value of the bottom solution at 7 ± 0.5; after adding, age for 2 h, keep stirring and water bath heating during the aging process; after the aging, wash the precipitate with deionized water until no sodium ions are detected in the filtrate; then, heat the precipitate at 110 o C for 12 h to obtain the precursor; S5: Grind the precursor into powder and heat it in air at 350 o C was calcined for 4 h at a heating rate of 3 o C / min; S6: After calcination, the catalyst was crushed into 40-60 mesh granular catalyst, which was mixed evenly with 1.55 g of 40-60 mesh silicon carbide and heated at 250°C in a 10% H2-90% N2 atmosphere. o C for 3 h, and the heating rate was 3o C / min to obtain a directly mixed catalyst.
[0046] Comparative Example 4 S1: First, add 14.50 g of copper nitrate trihydrate, 8.92 g of zinc nitrate hexahydrate, and 3.75 g of aluminum nitrate nonahydrate in a molar ratio of 6:3:1 to 100 g of water and stir to mix thoroughly; S2: Weigh 10.70 g of sodium carbonate (the same number of moles as the total number of the three metals) into 100 g of water and stir to mix thoroughly.
[0047] S3: Use 100 mL of deionized water as the precipitation base solution; S4: Add the metal salt solution of step S1 and the sodium carbonate solution of step S2 to the precipitation bottom solution of step S3 at the same time, stirring and stirring at 70 o C water bath and maintain the pH of the bottom solution at 7 ± 0.5; after adding, age for 2 h, keep stirring and water bath heating during the aging process; after the aging, wash the precipitate with deionized water until no sodium ions are detected in the filtrate; then heat the precipitate at 110 o C for 12 h to obtain the precursor; S5: Grind the precursor into powder and heat it in air at 350 o C was calcined for 4 h at a heating rate of 3 o C / min; S6: The calcined catalyst was then mixed with 1.55g of powdered silicon carbide and crushed to obtain a 40-60 mesh granular catalyst. The catalyst was heated at 250°C in a 10% H2-90% N2 atmosphere. o C for 3 h, and the heating rate was 3 o C / min to obtain a tableted mixed catalyst.
[0048] Comparative Example 5 S1: First, add 14.50 g of copper nitrate trihydrate, 8.92 g of zinc nitrate hexahydrate, and 3.75 g of aluminum nitrate nonahydrate in a molar ratio of 6:3:1 to 100 g of water and stir to mix thoroughly; S2: Weigh 10.70 g of sodium carbonate (the same number of moles as the total number of the three metals) into 100 g of water and stir to mix thoroughly; S3: Use 100 mL of deionized water as the precipitation base solution; S4: Add the metal salt solution of step S1 and the sodium carbonate solution of step S2 to the precipitation bottom solution of step S3 at the same time, stirring and stirring at 70 o C water bath and maintain the pH value of the bottom solution at 7 ± 0.5; after adding, age for 2 h, keep stirring and water bath heating during the aging process; after the aging, wash the precipitate with deionized water until no sodium ions are detected in the filtrate; then, heat the precipitate at 110o C for 12 h to obtain the precursor; S5: Grind the precursor into powder and heat it in air at 350 o C was calcined for 4 h at a heating rate of 3 o C / min; S6: The calcined catalyst was heated at 250°C in 10% H2-90% N2 atmosphere. o C for 3 h, and the heating rate was 3 o C / min, and obtain industrial copper-zinc-aluminum catalyst.
[0049] Table 1 shows the catalytic performance of the copper-zinc-aluminum catalysts prepared in various examples for methanol steam reforming to produce hydrogen.
[0050]
[0051] Comparison of Example 5 with Comparative Examples 1 and 2 shows that under the same conditions, the copper-zinc-aluminum catalyst obtained by using a suspension formed by silicon carbide and water as the precipitation bottom liquid has a higher methanol conversion rate of 48.5%. It is speculated that the hydrophilicity of the thermal conductor affects the degree of mixing of copper-zinc-aluminum and the thermal conductor, thereby affecting the catalytic activity of the catalyst.
[0052] Comparison of Example 5 with Comparative Examples 3 and 4 shows that when the thermal conductor is silicon carbide, the manner of adding copper, zinc, and aluminum mixed oxides to silicon carbide can significantly affect the catalytic activity of the catalyst, among which the catalyst prepared by the deposition co-precipitation method has the best catalytic activity. The catalyst thermal conductors obtained by the particle mixing and tablet mixing methods are not in close contact with the copper, zinc, and aluminum, and cannot better exert the high thermal conductivity of the thermal conductor.
[0053] Comparison of Example 5 with Example 6 and Example 8 shows that the catalytic activity of copper-zinc-aluminum catalyst prepared by different thermal conductors is different, among which graphite with high thermal conductivity (~ 129 W m -1 k -1 ) has the best catalyst activity, which is 51.1%; silicon carbide with medium thermal conductivity (~ 85 W m -1 k -1 ) had the second highest catalytic activity, at 48.5%; the lower thermal conductivity hydrophilic silica (~ 20 W m -1 k -1 ) has a low activity of 43.2%, which proves that the stronger the thermal conductivity of the thermal conductor, the more heat the catalyst absorbs from the outside, thereby promoting the occurrence of the highly endothermic methanol steam reforming reaction.
[0054] By comparing Example 5 with Example 9 and Example 11, it can be found that the methanol conversion rate of the catalyst remains basically unchanged when the type of metal salt is changed, indicating that the metal salt of this invention is easily soluble in water.
[0055] Comparing Example 5 with Examples 7 and 10, it can be seen that when all thermal conductors are silicon carbide, the amount of silicon carbide added also affects the final catalyst activity. The catalytic activity is highest when the SiC addition is 16.7%, while the catalytic activity decreases at lower SiC additions (5%) and higher SiC additions (37.5%). This is because the low SiC addition results in a negligible improvement in thermal conductivity, while the high SiC addition accounts for a relatively small proportion of the active component Cu in the catalyst. Therefore, the methanol conversion rate decreases when evaluating the methanol steam reforming reaction performance using the same catalyst mass.
[0056] pass Figure 1 The catalysts containing silicon carbide were found to exhibit a microscopic mixture of silicon carbide, copper, and zinc oxide nanoparticles. Comparing Examples 1-11 with Comparative Example 5, it was found that the copper-zinc-aluminum catalysts containing thermally conductive agents, prepared under different conditions, all showed improved catalytic activity compared to the catalyst without a thermally conductive agent. This demonstrates that the addition of a thermally conductive agent exerts varying degrees of effect, and that controlling the method and amount of thermally conductive agent addition can improve the performance of copper-zinc-aluminum catalysts containing a thermally conductive agent.
Claims
1. A high thermal conductivity core-shell copper-zinc-aluminum catalyst, characterized in that The catalyst has a core-shell structure, which includes a thermal conductor, copper, zinc oxide and aluminum oxide nanoparticles, wherein the thermal conductor is embedded between copper oxide, zinc oxide and aluminum oxide to form a catalyst structure with the thermal conductor as the core and the copper, zinc oxide and aluminum oxide nanoparticles as the shell.
2. A method for preparing a high thermal conductivity core-shell copper-zinc-aluminum catalyst according to claim 1, characterized in that The catalyst is prepared by a precipitation method, and the active component is in situ deposited on the surface of the thermal conductor, so that the thermal conductor is uniformly mixed with the catalyst active structure at the nanoscale to form a core-shell structure, with the thermal conductor as the core and the active component as the shell. The specific steps include: S1: Add the thermal conductive agent to a certain amount of deionized water and ultrasonically disperse it to obtain a suspension; S2: Dissolve the copper source, zinc source, and aluminum source in deionized water according to the feed ratio and stir evenly to obtain metal salt solution A; dissolve the alkali in deionized water to obtain solution B; S3: adding the metal salt solution A and solution B obtained in step S2 to the suspension obtained in step S1 in parallel, causing the metal salt to undergo an in-situ precipitation reaction on the thermal conductor. After the precipitation is completed, the mixture is aged under stirring. After the aging is completed, the mixture is filtered, washed, and dried to obtain a catalyst precursor. S4: calcining the precursor obtained in step S3 in a muffle furnace to obtain an oxidized copper-zinc-aluminum catalyst; The oxidized copper-zinc-aluminum catalyst is then subjected to a reduction treatment, and a core-shell copper-zinc-aluminum catalyst with high thermal conductivity is obtained after the treatment.
3. The method for preparing a high thermal conductivity core-shell copper-zinc-aluminum catalyst according to claim 2, characterized in that In step S1, the thermal conductive agent is one or more of silicon carbide, carbon black, silicon dioxide, graphite, copper powder, and iron powder, the mass fraction of the thermal conductive agent is 5-50%, and the particle size of the thermal conductive agent powder is less than 200 mesh.
4. The method for preparing a high thermal conductivity core-shell copper-zinc-aluminum catalyst according to claim 2, characterized in that In step S2, the copper source is one or more of copper acetate, copper nitrate, copper chloride, and copper sulfate; the zinc source is one or more of zinc acetate, zinc nitrate, zinc chloride, and zinc sulfate; the aluminum salt is one or more of aluminum nitrate, aluminum chloride, and aluminum sulfate; and the components in the catalyst are expressed in molar percentages as follows: Cu is 20-80%, Zn is 10-60%, and Al is 1-20%.
5. The method for preparing a high thermal conductivity core-shell copper-zinc-aluminum catalyst according to claim 2, characterized in that In step S2, the alkali is one or more of sodium hydroxide, sodium carbonate, sodium bicarbonate, ammonia water, etc., wherein the concentration of the alkali is 0.5-4 mol / L.
6. The method for preparing a high thermal conductivity core-shell copper-zinc-aluminum catalyst according to claim 2, characterized in that The specific process of step S3 is as follows: The metal salt solution A and solution B obtained in step S2 are added to the suspension obtained in step S1 at the same time, and the addition process is accompanied by stirring and 40-80 o C water bath heating and maintain the bottom liquid pH value at 6~8, after adding, aging for 0.5~4 h, keep stirring and water bath heating during the aging process, after the aging is completed, use deionized water to wash the precipitate until no sodium ions are detected in the filtrate, and then precipitate at 90~120 o C for 4 to 24 h to obtain a catalyst precursor.
7. The method for preparing a high thermal conductivity core-shell copper-zinc-aluminum catalyst according to claim 2, characterized in that The calcination temperature in step S4 is 300-500 o C, the calcination time is 2~6 h, the heating rate is 2~5 o C / min.
8. The method for preparing a high thermal conductivity core-shell copper-zinc-aluminum catalyst according to claim 2, characterized in that In step S4, the calcined oxidized copper-zinc-aluminum catalyst is treated in a reducing atmosphere. The treatment atmosphere is a diluted H2 atmosphere, wherein H2 accounts for 10%-50% of the volume ratio of the mixed gas, and the rest is an inert atmosphere of N2, Ar, and He. The heating rate is 2-5 o C / min, processing temperature is 200~300 o C, processing time is 2~4 h.
9. Use of a high thermal conductivity core-shell copper-zinc-aluminum catalyst prepared by the method according to any one of claims 2 to 8 in a methanol reforming hydrogen production reaction.
Citation Information
Patent Citations
Catalysts, their preparation methods and uses
CN103831131B
A metal porous thermally conductive catalyst system and a method for preparing glycolide at low temperature and pressure
CN116212950B
Cited By
A multi-level pore confined core-shell catalyst, and a preparation method and application thereof
CN122517024A